FORMULATION DEVELOPMENT AND STATISTICAL OPTIMIZATION OF IVABRADINE HYDROCHLORIDE FLOATING PULSATILE PELLETS BY FLUIDIZED BED COATING TECHNIQUE - Tubati, Vani Prasanna; Murthy Te, Gopala Krishna; Rao A, Samba Siva (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the current work was to develop Ivabradine hydrochloride (HCl) floating pulsatile pellets containing drug loaded calcium alginate pellets coated with pH-dependent polymer Eudragit S100 oil dispersion. Methods: Fluidized bed coating technique was used to develop pellets. A 2 factorial design was employed to study the effect of independent variables (inlet air temperature, spray rate), on dependent variables (% entrapment efficiency, % friability, and average particle size). Optimization was done by fitting experimental data to the software program (Minitab). Obtained pellets were subjected to different evaluation parameters which are critical in the development of the dosage form. An in vitro lag phase study was carried out for all batches in simulated gastric fluid (0.1N HCl) for 5 hrs and in vitro drug release study was carried out for optimized batch (B4) of two different sizes (10/12#, 12/16#) in simulated intestinal fluid (pH 7.4 phosphate buffer). 2 Results: The optimized batch (B4) showed satisfactory % entrapment efficiency of 92.66±1.52; % friability of 0.57±0.03; and average particle size of 1424±16 (µm). All batches maintained lag phase for 5 hrs in 0.1N HCl. An optimized batch of two different sizes exhibited a burst release within 30 minutes in simulated intestinal fluid with no significant difference in release rate constant (*p>0.05) and followed first order kinetics. Conclusion: Thus, ivabradine HCl floating pulsatile pellets was successfully developed for treating angina pectoris which is an underlying cause of heart attack by fluidized bed coating technique employing factorial design. Keywords: Ivabradine hydrochloride, Sodium alginate, Eudragit S100, Pellets, Fluidized bed coating, Optimization, Central composite design